The ecological genetics of Pseudomonas syringae in the kiwifruit phyllosphere : a thesis submitted in partial fulfilment of the requirements for the degree of Ph.D. in Evolutionary Genetics, New Zealand Institute for Advanced Study at Massey University, Auckland, New Zealand - Straub, Christina (Massey University, 2017)
The impact of disease-causing bacteria on their hosts is shaped by interactions with co-occurring microbes, but such interactions are rarely studied. Pseudomonas syringae is a ubiquitous and significant plant pathogen infecting a wide range of plants, often of agricultural importance. The community context of P. syringae in infected plant hosts has been little explored. I determined the population structure and genetic diversity of Pseudomonas syringae strains collected from infected and uninfected orchards over the course of a growing season during the current outbreak of bacterial canker of kiwifruit (P. syringae pv. actinidiae, Psa) in New Zealand. A total of 148 strains comprising Phylogroups 1, 2, 3 and 5 were characterised by Multi Locus Sequence Typing (MLST). The overall population structure was clonal, but with a low level of recombination for single housekeeping genes within phylogroups. More than half of the isolates belonged to a new Phylogroup 3 clade (PG3a) that was also commonly found on kiwifruit leaves in China and previously reported from kiwifruit leaves in Japan. To understand the ecological basis of the co-occurrence of PG3a and PG1 (Psa) I looked for evidence of niche specialisation by performing reciprocal invasion from rare assays of a selected representative from each lineage both in vitro and in planta. P. syringae G33C (PG3a) demonstrates antagonistic behaviour towards Psa NZ54, whereas Psa NZ54 exhibits a beneficial effect on growth of P. syringae G33C; an effect that could not be attributed to virulence activity encoded by the Type 3 Secretion System. Given this antagonistic behaviour, I explored the virulence repertoire in these commensal strains to determine their potential in the emergence of future more virulent types of Psa. In addition, I used comparative genomics to unravel the phylogenetic resolution of the novel P. syringae clade in context with known representatives of P. syringae PG3. Together my data draw attention to the community context of disease and demonstrate the value of incorporating an ecological dimension into the study of the genetic structure of pathogen populations.
Keywords: Pseudomonas syringae|; Genetics; Evolutionary genetics; Kiwifruit; Diseases and pests; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Genetics